Seismogenic fault system of the Mw 6.4 November 2019 Albania earthquake: new insights into the structural architecture and active tectonic setting of the outer Albanides. Issue 2 (2021) - Teloni, Simone; Invernizzi, Chiara; Mazzoli, Stefano; Pierantoni, Pietro Paolo; Spina, Vincenzo
No abstract available